Democracy in Latin America: Economic Liberalization, Populism, and Crisis - Rodríguez Echeverría, Miguel Ángel (2011)
After 1979, Latin America adopted broadbased reforms, abandoning importsubstitution industrialization for an export oriented development strategy and simultaneously adopting democratic forms of government. The new economicpolicies of open trade, balanced public budgets, monetary orthodoxy, exchange rate neutrality and more competitive and free internal markets are established at the same time that democracies start to operate in the Latin American Republics. What are the interactions between economic and political reforms? Is the simultaneity of economic and political institutions the cause of the disenchantment with democracy at the beginning of the XXI Century? This article analysizes these questions andreaches a negative answer. The thesis that complete and rational transformations are not possible determines that institutions must be transformed by marginal, gradual, evolutionary change, supported by strong coalitions of citizens. The futureof democracy and open markets in the region depends on reinforcing political and economic institutional transformations, supported by broad coalitions that piecemeal evolve to more open organizations.